Zastosowanie Podatności Szerokopasmowej do Oceny Reakcji Obietków Mechanicznych na Dowolne Wymuszenie - Cempel, C. (Engineering Transactions, 1973)
In the previous paper [1], the so-called «wide-band response» (mobility) of an arbitrary mechanical object was introduced. It is proved now that magnitude may be expressed as a function of certain parameters of the mechanical object frequency characteristics. Once the wide-band receptance and the spectral density of excitation are known, object's response to an arbitrary, excitation of a known spectrum may be either calculated or estimated. Experimental verification presented demonstrates a good agreement between the theoretical predictions and experimental data.